Ghana: Naga women, ICTs and natural resource management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Joana Francis Adda describes how an NGO in Ghana is using video equipment to enable women to devise community plans for natural resource management.